The Power Output and Sprinting Performance of Young Swimmers - Barbosa, Tiago M. (2020)
The aim of this article was to compare swimming power output between boys and girls and to model the relationship between swimming power output and sprinting performance in young swimmers. One hundred young swimmers (49 boys and 51 girls, aged between 11 and 13 years) underwent a test battery including anthropometrics (body mass, height, arm span [AS], and trunk transverse surface area), kinematic and efficiency (velocity, stroke frequency, stroke length, speed fluctuation, normalized speed fluctuation, stroke index, and Froude efficiency), hydrodynamics (active drag and active drag coefficient), and power output (power to overcome drag, power to transfer kinetic energy to water, and external power) assessments and sprinting performance (official 100 freestyle race). All variables but the trunk transverse surface area, stroke length normalize to AS, speed fluctuation, active drag coefficient, and Froude efficiency were significantly higher in boys than in girls with moderate-strong effects. Comparing both sexes but controlling the effect of the sprinting performance, most variables presented a no-significant variation. There was a significant and strong relationship between power output and sprinting performance: y = 24.179x (R = 0.426; standard error of estimation = 0.485; p < 0.001). As a conclusion, boys presented better performances than girls because of their higher power output. There is a cubed relationship between power output and sprinting performance in young swimmers.